Descentralizacion y participacion: dos variables democraticas tensiones y distennsiones en el sector salud, referencias a Brasil y Colombia - Gonzalez, Norha Cecilia Manotas (1997)
The mam purpose of this study is the decentralization analysis and the participation as democratical categories of the State's rearrangement specialy in the field of health policy in Brazil and Colombia. A theorical analysis was accomplished on the both categories and it's impact in the reformation of the relationship between State and society in order to examine it's conjunction on the reformulation, implementation and control of the health policys. The results founded allowed us to elaborated na analitical landmark of gradation leveI' s of decentralization and participation as well as the significances of these in the practice of a more democratical health management.